1031 IMPACT OF PRE-TREATMENT WITH A P2Y12 RECEPTOR INHIBITOR ON PERIPROCEDURAL MYOCARDIAL INFARCTION AND MYOCARDIAL INJURY IN NSTEMI. (15th December 2022) - Armillotta, Matteo; Bergamaschi, Luca; Sansonetti, Angelo; Stefanizzi, Andrea; Fabrizio, Michele; Angeli, Francesco; Amicone, Sara; Bodega, Francesca; Canton, Lisa; Suma, Nicole; Fedele, Damiano; Impellizzeri, Andrea; et al.
Abstract: Background: Dual antiplatelet therapy with aspirin and a P2Y12 receptor inhibitor is the standard of care in patients with acute coronary syndromes. The optimal timing of the administration of oral P2Y12 inhibitors has been largely debated, particularly among patients with non-ST-segment elevation myocardial infarction (NSTEMI). The latest European Society of Cardiology guidelines, based on recent scientific evidence, do not recommend routine pre-treatment with a P2Y12 inhibitor before coronary angiography. However, the impact of pre-treatment on the incidence of peri-procedural myocardial infarction (MI) and myocardial injury has never been explored. Purpose: To evaluate the impact of pre-treatment with a P2Y12 receptor inhibitor on periprocedural myocardial infarction and injury in NSTEMI patients undergoing invasive treatment. Methods: We evaluated all consecutive patients admitted to our coronary care unit from 2016 to 2021 affected by NSTEMI undergoing invasive management with percutaneous coronary intervention (PCI). We enrolled only patients with stable (≤ 20% variation) or falling pre-procedure baseline cardiac troponin (cTn) values. The entire population was divided into two groups: patients pre-treated with dual antiplatelet therapy (an oral P2Y12 inhibitor in adjunct to aspirin) before performing coronary angiography (upstream group) and patients who started an oral P2Y12 inhibitor only after PCI (downstream group). All patients received aspirin and anticoagulant therapy before coronary angiography. The primary endpoint was the incidence rate of periprocedural MI and myocardial injury according to the fourth universal definition of myocardial infarction. Finally, a safety endpoint of major and minor bleeding according to Thrombolysis in Myocardial Infarction (TIMI) criteria was evaluated for all bleeding episodes during hospitalization. Results: A total of 878 patients with NSTEMI undergoing PCI and with pre-procedure stable cTn levels were analyzed: 615 (70%) constituted the upstream group. The mean age of the study population was 70.1±12.5 years and 71.3% were males. There were no significant differences regarding traditional cardiovascular risk factors, comorbidities, cTn and hemoglobin levels between the two groups. After PCI, the rate of periprocedural myocardial injury and MI did not significantly differ between the upstream and downstream groups (19.5% vs 24.7%, p=0.08 and 17.6% vs 19.4%, p=0.5, respectively). A trend of lower periprocedural myocardial injury and MI cumulative incidence was observed in the upstream group (37.1% vs 44.1%, p=0.051). Notably, major and minor bleedings during hospitalization occurred more frequently in the upstream group compared to the downstream one (5.2% vs 1.9%, p=0.02). Conclusions: Among NSTEMI patients undergoing invasive management and with stable pre-procedure cTn levels, pretreatment with an oral P2Y12 inhibitor did not reduce the rate of periprocedural MI and myocardial injury but was associated with an increase in major and minor bleeding complications during hospitalization.